2015
DOI: 10.1080/14461242.2014.999402
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating the sick role: the experiences of high-risk women who undergo risk reducing breast surgery

Abstract: In recent years Talcott Parsons' work has come under renewed scrutiny by sociologists who argue that his concept of the sick role may have some role to play in current accounts of health and illness. In this paper we describe the ways in which Australian women who have undergone elective risk-reducing breast surgery (+/-ovarian surgery) talk about their convalescence. When describing their experiences women presented two contrasting recovery narratives in which the negative effects of breast surgery were eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Although the role excuses the sick from some societal responsibilities (e.g., work), there is the expectation that those occupying the role should seek to leave it as soon as possible (Parsons, 1951). While many criticisms have been leveled at the theory, our research found (as with other recent studies; Glenton, 2003;Hallowell et al, 2015) elements of the theory useful. Participants in our study (along with others; i.e., Harland et al, 2019) defined recovery not as being symptom free, but being able to resume certain societal roles, such as being in paid employment and/or being able to undertake typical activities of daily living.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although the role excuses the sick from some societal responsibilities (e.g., work), there is the expectation that those occupying the role should seek to leave it as soon as possible (Parsons, 1951). While many criticisms have been leveled at the theory, our research found (as with other recent studies; Glenton, 2003;Hallowell et al, 2015) elements of the theory useful. Participants in our study (along with others; i.e., Harland et al, 2019) defined recovery not as being symptom free, but being able to resume certain societal roles, such as being in paid employment and/or being able to undertake typical activities of daily living.…”
Section: Discussionsupporting
confidence: 76%
“…For example, neoliberalism emphasizes individual responsibility when managing and maintaining one's health (Vassilev et al, 2017). Rather than submitting to medical experts, patients are increasingly expected to self-manage their condition to minimize (costly) health professional contact (Hallowell et al, 2015). In addition, rather than the sick role being bestowed (or not) by physicians, individuals are seen as having an active role in narrating (i.e.…”
Section: Theory: the Sick Rolementioning
confidence: 99%
See 1 more Smart Citation
“…This research has done much to illuminate the politics involved in expert efforts to identify and control particular (personal, environmental and/or cultural) factors understood to increase the prevalence of disease in targetable groups or communities (Herrick, 2007; Hyde, 2011; Kent and Farrell, 2014; Wentzell, 2011). It has also provided insight on how lay individuals interpret, rework and contribute to expert conceptualizations of bodily risks, especially as they relate to risks of becoming ill (Hallowell et al, 2015; Lock, 2005; Morden et al, 2012; Novas and Rose, 2005). Such studies have convincingly demonstrated that bodily risks are not experienced or governed uniformly: the perception and identification of risk factors indicating a higher chance of acquiring a disease, and the ability to develop ways of responding to, or minimizing, those risks, vary greatly according to the individual’s particular condition, her life history and her socioeconomic, not to mention cultural, background.…”
mentioning
confidence: 99%